2022
DOI: 10.1177/03000605221108924
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity as a biomarker for the diagnosis of lung cancer in high-risk patients

Abstract: Objective Natural killer (NK) cells play an essential role in the immune response against cancer. However, immune escape mechanisms may cause inferior NK cell activity (NKA) in patients with cancer. This prospective study examined the relationship between NKA and lung cancer in a high-risk cohort. Methods In a cohort study, 250 participants referred by their general practitioner for suspicion of lung cancer were included. Before clinical investigation, blood was collected into NK Vue tubes, and the level of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…However, NK cells also play a key role in preventing tumor progression and metastasis through their direct cytotoxic activity and secreted cytokines [ 47 ]. Recent studies have shown that low NKA is significantly associated with a higher risk of various cancers, such as hepatocellular carcinoma [ 36 ], colorectal cancer [ 48 ], head and neck squamous cell carcinoma [ 49 ], lung cancer [ 50 ], and pancreatic cancer [ 51 ]. Jun’s study showed that NKA is progressively impaired during tumor development, and its dysfunction is associated with recurrence and survival outcomes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, NK cells also play a key role in preventing tumor progression and metastasis through their direct cytotoxic activity and secreted cytokines [ 47 ]. Recent studies have shown that low NKA is significantly associated with a higher risk of various cancers, such as hepatocellular carcinoma [ 36 ], colorectal cancer [ 48 ], head and neck squamous cell carcinoma [ 49 ], lung cancer [ 50 ], and pancreatic cancer [ 51 ]. Jun’s study showed that NKA is progressively impaired during tumor development, and its dysfunction is associated with recurrence and survival outcomes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer cell activity was measured in whole blood using the NK Vue ® assay (NKMAX Co Ltd, Seongnam-si, South Korea) that consists of a special sample tube and an ELISA. The analyses were performed at the Department of Clinical Biochemistry, Lillebaelt Hospital Vejle -University Hospital of Southern Denmark, Denmark and has been described previously (82). Besides Na-heparin as the anticoagulant, the NK Vue ® tubes hold an NK cell-stimulating agent, Promoca ® .…”
Section: Natural Killer Cells Activitymentioning
confidence: 99%
“…When applying the USPSTF screening criteria, detection of stage I-II vs. stage III-IV were equally low, with AUC values of 0.62 and 0.61, respectively. The ability of NKA to detect all-stage lung cancer and late-stage lung cancer was assessed using ROC curves (Figure 12) (82). The AUC for detecting any stage of lung cancer was 0.57 (95% CI: 0.49-0.66), while the AUC for detecting late-stage lung cancer was 0.66 (95% CI: 0.57-0.75).…”
Section: Study 2: Biomarker Panel (Cyfra 21-1 Cea Ca125)mentioning
confidence: 99%
See 2 more Smart Citations